The Extended Producer Responsibility for Waste Oils - Arner Guerre, Asuncion (International Journal of Energy Economics and Policy, 2022)
Currently, lubricants producers, electrical, electronic producers, and cars producers share waste oil management responsibility. The extended producer responsibility (EPR) regime for WEEE was updated to incorporate the mandate of using economic incentives correctly regarding applying the hierarchy principle in WEEE management. Moreover, EPR on end on life vehicles (ELV) was updated to accomplish the hierarchy principle. This work aims to evaluate the scope of EPR for waste oils, for which other producer responsibility organizations (PROs) have responsibility. The method consists in estimating first the cointegrating equation for the variables lubricating oil production (LP) and oil price (FRP) using Dynamic Least Squares Estimator (DOLS) for the period 2007-2020. Subsequently, the cointegrating equation between the variables LP and electric domestic appliances with oils (AWO) and LP and vehicles production (VP) are estimated using DOLS. The main results show that the variables LP and FRP are cointegrated. Besides, the elasticity of the LP variable up to FRP was negative at 0,45. In contrast, variables LP and AWO, neither LP nor VP, are not cointegrated. That context suggested that EPR for waste oils should be considered to join other economic incentives.